Innovation Drivers and Outputs for Software Firms: Literature Review and Concept Development. (10th April 2016) - Rose, Jeremy; Furneaux, Brent
Abstract : Software innovation, the ability to produce novel and useful software systems, is an important capability for software development organizations and information system developers alike. However, the software development literature has traditionally focused on automation and efficiency while the innovation literature has given relatively little consideration to the software development context. As a result, there is a gap in our understanding of how software product and process innovation can be managed. Specifically, little attention has been directed toward synthesizing prior learning or providing an integrative perspective on the key concepts and focus of software innovation research. We therefore identify 93 journal articles and conference papers within the domain of software innovation and analyse repeating patterns in this literature using content analysis and causal mapping. We identify drivers and outputs for software innovation and develop an integrated theory-oriented concept map. We then discuss the implications of this map for future research.